Great teachers of Gaspare Tagliacozzi (1546–1599). (August 2017) - Gurunluoglu, Raffi; Gurunluoglu, Aslin; Arton, Jamie
Gaspare Tagliacozzi successfully practised the art of plastic surgery in the sixteenth century and conducted a long series of precise observations on the basis of which he formulated detailed principles for rhinoplastic. He wrote the first complete description of nasal reconstruction using skin from the arm. Tagliacozzi's teachers at the University of Bologna during his student days remain largely unfamiliar, Giulio Cesare Aranzio, Ulisse Aldrovandi and Girolamo Cardano. Aldrovandi taught the 'ordinary', that is the principal course in natural philosophy. Aranzio taught the chief course in surgery and anatomy. Cardano taught a course in the theory of medicine. Their activity contributed to the slow move from Galenic teaching in medicine and the static acceptance of tradition in all science.